A Transatlantic history of public administration Analyzing the USA, Germany, and France - Sager, Fritz; Rosser, Christian; Mavrot, Celine; Hurni, Pascal Y. (Cheltenham, UK Edward Elgar, 2018)
Offering a thorough analysis of the transatlantic history of Public Administration, the conclusion argues that it is vital to learn from the past, in order to make Public Administration more realistic in theory, as well as more successful in practice.
1. Introduction: why study the transatlantic history of administrative ideas? -- 2. Setting the scene: the administrative traditions of Germany, France and the USA -- 3. Examining the scene: the transfer-of-ideas approach applied to the history of administrative traditions -- 4. The transfer of knowledge from Germany and France to the USA -- 5. The import of US ideas by German Public Administration -- 6. The transfer of knowledge from the USA to France -- 7. Public Administration in Germany, France and the USA: traditional flavors or hybrid traditions? -- 8. Lessons learned: making administrative theory more realistic and administrative practice more successful.
Includes bibliographical references and index
Keywords: Public administration -- Europe,Western -- History; Public administration -- United States; Public administration -- Germany -- History; Public administration -- France -- History